Pengembangan Permainan Scrabble Kimia Sebagai Media Pembelajaran Pada Materi Termokimia Kelas XI SMA atau MA - Silvinia Humaira; Fajriah Azra (Edukimia, 2021)
The chemical scrabble game is a variety of learning media in doing practices. This type of research is Research and Development (R and D) with a 4-D model. This research is up to the developing stage with validity and practicality tests. The instrument used was a validity and practicality questionnaire. The validity test was carried out by five validators, while the practicality test was carried out by two chemistry teachers and 20 class XII students. The data analysis techniques used were the Aiken V formula and descriptive statistics. The results of the data analysis show that the chemical scrabble media has a validity of 0.81 showing a valid category, the practicality of the teacher is 89.93 percent belonging to a very practical category and the practicality of students is 83.80 percent belonging to a very practical category, so that the availability of the developed thermochemical scrabble game chemicals can be used as a medium of learning.